Rethinking the “Golden Age”: Jewish-Christian Relations in Pre-Modern Poland - Teter, Magda (Studies in Christian-Jewish Relations, 2011)
This paper addresses the question of the “golden age” present in Polish and Jewish historiographies. It demonstrates that though the idea of the “golden age” was embraced by both Polish Christian and Jewish historians, they never applied it to Jewish-Christian relations. This paper looks at the myths of the golden age and the age of decline in both historiographies by juxtaposing them with archival documents that complicate both the idea of the “zenith” or “golden age” of the 16th century and that of the decline and crisis of the 17th century.